Análisis del riesgo de introducción del Viroide ASBVd (Avocado Sunblotch Viroid ) causante de la mancha solar del aguacate ( Persea americana ) plaga cuarentenaria para Ecuador. - Paredes Valdivieso, Marco Rolando (2021)
The avocado (Persea americana) is a fruit that in recent years has attracted the attention of international markets for its nutritional and cosmetic properties. Ecuador, as a producer country, needs to renew its commercial plantations with varieties that are in demand in these markets. Countries such as Mexico and Peru can provide the vegetative material for this purpose, but they have in their territories a pest that in our country it is a quarantine one. This pest is called the Avocado Sunblotch Viroid (ASBVd) that causes Avocado Sunblotch disease, which causes damage to fruit, branches, bark and can be transmitted by vegetative material, seed, pollen and work tools. The “Organización Nacional de Protección Fitosanitaria” (ONPF) of Ecuador, the “Agencia de Regulación y Control Fito y Zoosanitario”, issued under resolution 002 in 2020, a Guide for the conduct of Pest Risk Analysis by Pest, which is the basis for this research project. The application of the guide made it possible to identify the phytosanitary measures necessary to mitigate the risk of ASBVd in Ecuadorian territory. These phytosanitary measures are as follows: Sourcing of propagative material from an area free of ASBVd in compliance with ISPM 4; verification at origin of the material to be imported by the NPPO; official laboratory diagnosis of the absence of viroid symptomatology in the material to be imported; Phytosanitary Export Certificate (PEC) with a statement indicating that the material comes from an area free of ASBVd; the material will be subject to post-entry quarantine